Assembling nature as an art object: A single video case analysis of two landscape artists navigating social context - Baddeley, Maximilon (Social Interaction. Video-Based Studies of Human Sociality, 2020)
Using video data obtained from a one-day field ethnography, I utilised the ethnomethodological respecification of ‘gestalt-contextures’ to describe in fine detail how two artists and a social researcher haphazardly organised themselves to navigate river terrain. The art object took on many meanings within the ongoing context of the group’s verbal and non-verbal, vernacular, and expert ability to observe the subject matter. Whilst organising join-attention to an array of natural objects, the participants defined pathway limitations, and rerouted, reviewed and positioned their bodies amongst the landscape. These socially acknowledged features typically remain unexposed when art sociologists discuss ‘artwork’. Due to the value of understanding the production of artistic objects in, and as a variety of socially maintained endogenous orders, the reportage of ‘gestalt assembly’ may furnish ‘the new sociology of art’ with materials for pursuing an alternative style of social research: the investigation of ordinary social context as member’s ongoing enacted achievement.